Analysis of the 2024 accreditation assessment instrument on school performance based on national education standards - Hironimus Tangi; Agus Timan; Aan Fardani Ubaidillah (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2026)
This study evaluates the alignment of the 2024 accreditation instrument by the National Accreditation Board for Primary and Secondary Education (BAN-PDM) with the National Education Standards mandated in Government Regulation No. 4 of 2022. Utilising a qualitative library research methodology, data were systematically gathered through comprehensive literature reviews of relevant electronic media, academic publications, and official documents. The analysis assessed ten fundamental indicators derived from the National Education Standards against the new accreditation framework. The findings reveal a significant disparity in standard fulfilment. Specifically, only two of the evaluated aspects—the Learning Process Standards and the Facilities and Infrastructure Standards—are adequately met by the 2024 BAN-PDM instrument. Conversely, the remaining eight critical areas are not fully met. These inadequately addressed areas encompass Graduate Competency, Content, Educational Assessment, Educators and Education Personnel, Management, and Financing Standards. Furthermore, the essential mandate for a comprehensive school-based quality assurance process, which involves continuous development, monitoring, and reporting by education units, remains unfulfilled in the current instrument. In conclusion, the 2024 accreditation instrument is predominantly out of alignment with the broader National Education Standards, underscoring a critical need for structural revisions to ensure holistic educational quality improvement across primary and secondary education levels.